A prospective, randomized, single-blind, multicentre, phase III study on organ preservation with Custodiol-N solution compared with Custodiol solution in organ transplantation (kidney, liver and pancreas) - Kniepeiss, Daniela; Houben, Philipp; Stiegler, Philipp; Berghold, Andrea; Riedl, Regina; Kahn, Judith; Schemmer, Peter (Trials, 2020)
Organ preservation before transplantation is still a challenge. Both the University of Wisconsin and Bretschneider’s histidine-tryptophan-ketoglutarate (HTK; Custodiol®) solution are standard for liver, kidney and pancreas preservation. Organ preservation with both solutions is comparable; recently, however, Custodiol® solution has been modified to Custodiol-N according to the needs of today. Thus, our study was defined to study its effect in clinical transplantation.
Gesehen am 26.03.2020